2016
DOI: 10.1002/ange.201609662
|View full text |Cite|
|
Sign up to set email alerts
|

Nickel‐Catalyzed Barton Decarboxylation and Giese Reactions: A Practical Take on Classic Transforms

Abstract: Tw on amed reactions of fundamental importance and paramount utility in organic synthesis have been reinvestigated, the Barton decarboxylation and Giese radical conjugate addition. N-hydroxyphthalimide (NHPI) based redox-active esters were found to be convenient starting materials for simple,t hermal, Ni-catalyzed radical formation and subsequent trapping with either ah ydrogen atom source (PhSiH 3 )o ra ne lectron-deficient olefin. These reactions feature operational simplicity,i nexpensive reagents,a nd enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 55 publications
0
49
0
Order By: Relevance
“…On the basis of the above results and literature precedent, [6][7][8][9] we propose the reaction mechanism in Scheme 3. [a] Reaction conditions: redox-active ester (0.2 mmol), R 2 Zn (0.66 mmol), CoBr 2 (20 mol %), in DMF (0.4 m), room temperature, 15 h; yields are for the isolated product.…”
Section: Angewandte Chemiementioning
confidence: 83%
See 2 more Smart Citations
“…On the basis of the above results and literature precedent, [6][7][8][9] we propose the reaction mechanism in Scheme 3. [a] Reaction conditions: redox-active ester (0.2 mmol), R 2 Zn (0.66 mmol), CoBr 2 (20 mol %), in DMF (0.4 m), room temperature, 15 h; yields are for the isolated product.…”
Section: Angewandte Chemiementioning
confidence: 83%
“…The method enabled efficient alkylaryl, alkyl-alkenyl, and alkyl-alkynyl coupling reactions under mild reaction conditions with no external ligand or additive needed. [5] Advances by the Baran research group showed that low-valent first-row transition metals,i ncluding nickel [6] and iron, [6h,g, 7] were also effective in abroad range of decarboxylative cross-coupling reactions without the need for light irradiation. Mechanistic studies indicated that aradical mechanism is involved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…109,110 Focusing instead on postassembly synthetic transformations, it is unsurprising that the aforementioned chemoselectivity challenges (see the discussion of Asp and Glu in Polar, Ionizable Side Chains) apply to α -carboxylic acids as well. Nevertheless, orthogonal protecting group strategies and judicious sequence choice have been employed to enable several decarboxylative functionalizations of α -acids, including 1,4-additions (entry 44), 79 heteroarylations (entry 45), 80,81 and borylations (entry 46). 82 …”
Section: C-terminus and N-terminusmentioning
confidence: 99%
“…Redox‐active esters were either isolated or formed in situ and then reacted with a nickel or iron catalyst and one of the eight ligands, L1–L8, shown in Figure . The majority of the reactions described in this review used ligands L1, L2, L3, or L5 . During the reaction, redox‐active esters react with the nickel or iron catalyst to eliminate carbon dioxide through electron transfer redox chemistry to generate a radical intermediate which reacts with various compounds to generate a wide range of products as shown in Scheme .…”
Section: Redox‐active Estersmentioning
confidence: 99%